Severe anemia in Papua New Guinean children from a malaria-endemic area: a case-control etiologic study. - Laurens Manning; Moses Laman; Anna Rosanas-Urgell; Pascal Michon; Susan Aipit; Cathy Bona; Peter Siba; Ivo Mueller; Timothy M E Davis (Public Library of Science (PLoS), 2012)
BACKGROUND: There are few detailed etiologic studies of severe anemia in children from malaria-endemic areas and none in those countries with holoendemic transmission of multiple Plasmodium species. METHODOLOGY/PRINCIPAL FINDINGS: We examined associates of severe anemia in 143 well-characterized Papua New Guinean (PNG) children aged 0.5-10 years with hemoglobin concentration <50 g/L (median [inter-quartile range] 39 [33]-[44] g/L) and 120 matched healthy children (113 [107-119] g/L) in a case-control cross-sectional study. A range of socio-demographic, behavioural, anthropometric, clinical and laboratory (including genetic) variables were incorporated in multivariate models with severe anemia as dependent variable. Consistent with a likely trophic effect of chloroquine or amodiaquine on parvovirus B19 (B19V) replication, B19V PCR/IgM positivity had the highest odds ratio (95% confidence interval) of 75.8 (15.4-526), followed by P. falciparum infection (19.4 (6.7-62.6)), vitamin A deficiency (13.5 (5.4-37.7)), body mass index-for-age z-score <2.0 (8.4 (2.7-27.0)) and incomplete vaccination (2.94 (1.3-7.2)). P. vivax infection was inversely associated (0.12 (0.02-0.47), reflecting early acquisition of immunity and/or a lack of reticulocytes for parasite invasion. After imputation of missing data, iron deficiency was a weak positive predictor (6.4% of population attributable risk). CONCLUSIONS/SIGNIFICANCE: These data show that severe anemia is multifactorial in PNG children, strongly associated with under-nutrition and certain common infections, and potentially preventable through vitamin A supplementation and improved nutrition, completion of vaccination schedules, and intermittent preventive antimalarial treatment using non-chloroquine/amodiaquine-based regimens.